2022
DOI: 10.3390/toxins14080532
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Differences in the Venom of Crotalus durissus cumanensis from Colombia

Abstract: Biochemical and biological differences in the venom of Crotalus durissus cumanensis from three ecoregions of Colombia were evaluated. Rattlesnakes were collected from the geographic areas of Magdalena Medio (MM), Caribe (CA) and Orinoquía (OR). All three regionally distributed venoms contain proteases, PLA2s and the basic subunit of crotoxin. However, only crotamine was detected in the CA venom. The highest lethality, coagulant, phospholipase A2 and hyaluronidase activities were found in the MM venom. Also, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 88 publications
0
0
0
Order By: Relevance
“…Regarding geographical variability, Rodriguez-Vargas et al [54] identified differences between C. d. cumanensis from different eco-regions of Colombia. The main finding was the presence of crotamine only in venoms from the Caribbean region.…”
Section: Crotalus Durissus Cumanensismentioning
confidence: 99%
“…Regarding geographical variability, Rodriguez-Vargas et al [54] identified differences between C. d. cumanensis from different eco-regions of Colombia. The main finding was the presence of crotamine only in venoms from the Caribbean region.…”
Section: Crotalus Durissus Cumanensismentioning
confidence: 99%